The Global Significance of Integrated Studies Based on SDGs in Japan - Katsuhisa Shirai (IAIN Madura, 2026)
Education for Sustainable Development (ESD) plays a crucial role in equipping learners with the competencies needed to address global sustainability challenges and achieve the Sustainable Development Goals (SDGs). Japan has demonstrated strong performance in both SDG implementation and the Programme for International Student Assessment (PISA), raising interest in the educational factors underlying these achievements. This study examines the contribution of Integrated Learning Time, an inquiry-based and interdisciplinary learning framework in the Japanese curriculum, to the development of sustainability competencies and academic performance. Using a qualitative document analysis approach, data were collected from MEXT policy documents, OECD reports, PISA 2022 results, the Sustainable Development Report 2025, and relevant scholarly literature. The findings indicate that Integrated Learning Time promotes critical thinking, problem-solving, collaboration, and global citizenship through authentic, real-world learning experiences. These competencies align closely with the principles of ESD and contribute to both educational quality and sustainable development outcomes. The study concludes that Integrated Learning Time offers a valuable model for integrating sustainability education with academic excellence and may provide insights for educational reform in other countries